2021
DOI: 10.1080/11035897.2021.1895303
|View full text |Cite
|
Sign up to set email alerts
|

First discovery of Small Shelly Fossils and new occurrences of brachiopods and trilobites from the early Cambrian (Stage 4) of the Swedish Caledonides, Lapland

Abstract: New fossil discoveries are reported from the Grammajukku Formation at Luobákte south of Lake Torneträsk in northern Swedish Lapland, including a fauna of Small Shelly Fossils (SSF) from a limestone bed in the uppermost part of the formation and new occurrences of brachiopods and trilobites in siltstones of the lower part of the formation. The moderately diverse SSF fauna is the first of its kind reported from the Swedish Caledonides and includes the first record of the tommotiid Lapworthella schodackensis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…reported from the uppermost early Cambrian strata in Skåne, Sweden (Bergström & Ahlberg 1981). Skovsted et al (2021) reported Eoobolus cf. priscus (Poulsen, 1932), from Swedish Lapland and suggested that several earlier reported lingulid specimens of similar age from Sweden were presumably conspecific.…”
Section: Brachiopods (Fig 6)mentioning
confidence: 99%
See 3 more Smart Citations
“…reported from the uppermost early Cambrian strata in Skåne, Sweden (Bergström & Ahlberg 1981). Skovsted et al (2021) reported Eoobolus cf. priscus (Poulsen, 1932), from Swedish Lapland and suggested that several earlier reported lingulid specimens of similar age from Sweden were presumably conspecific.…”
Section: Brachiopods (Fig 6)mentioning
confidence: 99%
“…It is of large size, comparable to the Mjøsa specimens, and showing a highly raised and coneshaped ventral valve, reminiscent of the more flattened valves preserved in mudstone from the Skyberg Member. Skovsted et al (2021) reported Botsfordia cf. caelata from northern Swedish Lapland, approximately age-equivalent with the Skyberg Member, and suggested that the two taxa may be synonymized.…”
Section: Brachiopods (Fig 6)mentioning
confidence: 99%
See 2 more Smart Citations